Characterization of patients with aHUS and associated triggers or clinical conditions: a Global aHUS Registry analysis - Licht, Christoph; Al-Dakkak, Imad; Anokhina, Katerina; Isbel, Nicole; Frémeaux-Bacchi, Véronique; Gilbert, Rodney D.; Greenbaum, Larry A.; Ariceta, Gema; Ardissino, Gianluigi; Schaefer, Franz; Rondeau, Eric (Nephrology, 2024)
Introduction Atypical haemolytic uremic syndrome (aHUS) is a rare form of thrombotic microangiopathy (TMA) associated with complement dysregulation; aHUS may be associated with other ‘triggers’ or ‘clinical conditions’. This study aimed to characterize this patient population using data from the Global aHUS Registry, the largest collection of real-world data on patients with aHUS. Methods Patients enrolled in the Global aHUS Registry between April 2012 and June 2021 and with recorded aHUS-associated triggers or clinical conditions prior/up to aHUS onset were analysed. aHUS was diagnosed by the treating physician. Data were classified by age at onset of aHUS (< or ≥18 years) and additionally by the presence/absence of identified pathogenic complement genetic variant(s) and/or anti-complement factor H (CFH) antibodies. Genetically/immunologically untested patients were excluded. Results 1947 patients were enrolled in the Global aHUS Registry by June 2021, and 349 (17.9%) met inclusion criteria. 307/349 patients (88.0%) had a single associated trigger or clinical condition and were included in the primary analysis. Malignancy was most common (58/307, 18.9%), followed by pregnancy and acute infections (both 53/307, 17.3%). Patients with an associated trigger or clinical condition were generally more likely to be adults at aHUS onset. Conclusion Our analysis suggests that aHUS-associated triggers or clinical conditions may be organized into clinically relevant categories, and their presence does not exclude the concurrent presence of pathogenic complement genetic variants and/or anti-CFH antibodies. Considering a diagnosis of aHUS with associated triggers or clinical conditions in patients presenting with TMA may allow faster and more appropriate treatment.
Veröffentlicht: 11 April 2024
Gesehen am 02.10.2024